(untitled) (Global Journal of Management and Business Research, 2017)
Employee State Insurance (ESI) Scheme is a very large social security. It is different from other types of insurance like Health Insurance that it provides full amount of medical bill irrespectively of the premium contribution. The purpose of the study is to analysis the awareness and satisfaction with the level of Utilization of Employee State Insurance (ESI) policy. The study also attempt to review the various Employee State Insurance (ESI) benefits available to the Employees. The research paper is to find the effects of utilization of Employee State Insurance(ESI) policy using various statistical tool through SPSS software.